2021
DOI: 10.1007/s00253-020-11076-y
|View full text |Cite
|
Sign up to set email alerts
|

Datamining and functional environmental genomics reassess the phylogenetics and functional diversity of fungal monosaccharide transporters

Abstract: HAL is a multi-disciplinary open access archive for the deposit and dissemination of scientific research documents, whether they are published or not. The documents may come from teaching and research institutions in France or abroad, or from public or private research centers. L'archive ouverte pluridisciplinaire HAL, est destinée au dépôt et à la diffusion de documents scientifiques de niveau recherche, publiés ou non, émanant des établissements d'enseignement et de recherche français ou étrangers, des labor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 66 publications
0
2
0
Order By: Relevance
“…Surprisingly, 127 putative sugar transporters were found in the genome of A. oryzae (Lv et al 2020 ). On the other hand, the model yeast S. cerevisiae has only 25 sugar transporters in its genome, most of them (17) hexose transporters, two sensors, only three disaccharide transporters, and three polyol transporters (Barbi et al 2021 ; Donzella et al 2023 ). The basidiomycete Ustilago maydis , a pathogen of maize, also possesses a reduced number of sugar transporters (20), some of them capable of transporting pentoses and uronic acids, in contrast to S. cerevisiae (Wahl et al 2010 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Surprisingly, 127 putative sugar transporters were found in the genome of A. oryzae (Lv et al 2020 ). On the other hand, the model yeast S. cerevisiae has only 25 sugar transporters in its genome, most of them (17) hexose transporters, two sensors, only three disaccharide transporters, and three polyol transporters (Barbi et al 2021 ; Donzella et al 2023 ). The basidiomycete Ustilago maydis , a pathogen of maize, also possesses a reduced number of sugar transporters (20), some of them capable of transporting pentoses and uronic acids, in contrast to S. cerevisiae (Wahl et al 2010 ).…”
Section: Discussionmentioning
confidence: 99%
“…3 , cluster 4). With respect to the monosaccharide mannose, Barbi et al ( 2021 ) observed a close association between glucose and mannose transport and found that out of the 49 published glucose transporters, only five could not transport mannose, including the l -arabinose transporter LAT-1 from N. crassa . This observation suggests that some of the glucose transporters from N. crassa may indeed also transport mannose.…”
Section: Discussionmentioning
confidence: 99%